Právní aspekty asistované reprodukce - Zemandlová, Anna; Hrušáková, Milana, 1952-; Masarykova univerzita. Katedra občanského práva (2006)
Práce se zabývá problematikou asistované reprodukce a umělým oplodněním zejména z etického a právního hlediska. Je poskytnut přehled právních předpisů aplikovatelných de lege lata. Dále je uvažováno o nové právní úpravě v kontextu právních řádů některých zemí.
Twenty years ago, a procedure currently known as in vitro fertilisation has been successfully applied for the first time. Subsequently, Louisa Brown was born and she became the symbol of our fight with infertility. However, many ethical, religious, social and legal questions arose that have been discussed so far and that still are a matter of debate. This thesis entitled Legal Aspects of Assisted Reproduction is not limited to the statement that appropriate legislation is lacking. It also describes and analyses present legal regulations and possibilities of its practical application in specific situations.
Vedoucí práce: Milana Hrušáková.
Diplomová práce (Mgr.)--Masarykova univerzita, Právnická fakulta, 2006.
Keywords: asistovaná reprodukce; umělé oplodnění; artificial insemination; assisted reproduction; diplomové práce